(untitled) (Asian Journal of Medical and Biological Research, 2016)
The present study was conducted using growth performance data on 624 Brahman cross (25%) calves collected from three villages adjacent to Bangladesh Agricultural University, Mymensingh, Bangladesh. Growth performance data of 289 Brahman cross (50%) calves were also collected from record sheet maintained at 12 Upazila Livestock Offices under the "Beef breed development project" of Department of Livestock Services to compare performance between 25% and 50% Brahman cross calves. Growth performance traits were considered birth weight, weight at three-, six-, nine-, twelve-month of age, average daily gain from birth to twelve-month of age. Calving difficulties (dystocia) and calf mortality were also included in the study area. The birth weight, weight at three-, six-, nine- and twelve-month average daily gain for 25% Brahman cross calves were 19.79±0.20, 52.72±1.31, 86.61±2.02, 129.90±3.08, 172.60±3.48 kg and 426.00±4.99g, respectively. The average birth weight (21.40±0.24 kg) and twelve-month weight (229.62±2.08 kg) of 50% Brahman cross calves were significantly higher (p<0.05) than 25% Brahman cross calves. Average daily gain was significantly higher (570.52±5.19g) in 50% Brahman cross than 25% Brahman cross calves (529.98±4.54g). Birth weight, three-, six-, nine-, twelve-month weight were positively correlated to each other. Strong correlations were found between birth weight and three-month weight (0.65), between six- and nine-month (0.65).There was no report of calving difficulties or abnormal calf birth, where the average calf mortality rate was 2.96 in the study areas. It indicates that 50% Brahman cross calves were well performed in these climatic condition. However, further study with larger sample sizes covering more different management systems would be required to draw a better conclusion in this regard. Asian J. Med. Biol. Res. June 2016, 2(2): 259-265